Lillian Boxfish takes a walk [large type] : a novel - Rooney, Kathleen, 1980- (Thorndike Press, a part of Gale, Cengage Learning, 2017)
Inspired by Margaret Fishback, poet and Macy's ad-writing phenom of the 1930s, Rooney imagines an extraordinary walk through the streets of New York City on the last night of 1984, one that triggers a flood of memories for fictional ad woman Lillian Boxfish. The octogenarian muses on the changing urban landscape as she stops at favorite haunts: an intimate neighborhood bar that's just installed a TV, a restaurant where she's dined every New Year's Eve that's about to change owners, the famed Delmonico's, where she ended her marriage. Further stops include a changing lower Manhattan landscape where she meets a haunted Vietnam veteran and engages him in a "best last-line contest," a detour to a hospital emergency room with a frightened woman about to have her first baby, and a party where she's both scorned and adored by a new generation of artists, followed by a hilarious encounter with three muggers. Meanwhile, Lillian carefully recounts her celebrated career in advertising, her adored husband and son, and her emotional breakdown. Elegantly written, Rooney creates a glorious paean to a distant literary life and time-and an unabashed celebration of human connections that bridge the past and future.